Russia Conflict on Twitter: Social factors and polarity on users’ interactions - Perez-Cepeda, Maximiliano; Garcés-Silva, Magaly; Villacrés-Roca, Ricardo (Revista Venezolana de Gerencia, 2024)
In the aftermath of armed conflicts, societal expressions unfold through diverse communication channels, with Twitter. Individuals share these expressions, aiming for broader societal consumption, fostering interaction across impacted entities—individuals, businesses, organizations, and governments. This analytical endeavor aims to analyze interaction patterns responding to sociocultural factors and sentimentally charged content on Twitter in the context of the Russia-Ukraine conflict. This research employed a sequential mixed approach to examine social factors in user publications on Twitter and assess their impact on interactions, considering sentimental polarity. The qualitative phase involved netnographic exploration of a total of 2578 tweets, collected from users World Trade Organization since February 24, 2022, until March 31, 2022. The subsequent quantitative phase analyzed the relationship between social factors, sentimental polarity, and user interactions through decision tree analysis. The results show that notably, the categories MET-Mention (35.82%) and MSG-Message (35.82%) emerged as the most frequent Two interactions were the most common (52.5%). The primary theme discussed in the messages was Information with 52.99% of the twits. Negative polarity emerged as the factor triggering more engagement, resulting in higher interaction levels. The majority of interactions (52.5%) were characterized by two interactions. In conclusion, the dominance of the information category underscores the pivotal role of social media in disseminating information during global events. Furthermore, negative sentiment, is associated with conflict-related concerns, correlated with higher interaction levels.